Financial institutions in Malaysia: an introduction / Ruziah Latif, Tay Bee Hoong and Yuslizawati Mohd Yusoff - Latif, Ruziah; Tay, Bee Hoong; Mohd Yusoff, Yuslizawati (Penerbit UiTM Press, 2011)
This book is aimed as an additional tool of knowledge for such important areas as it does not only beneficial for students, but also to enrich readers' knowledge regarding Malaysian financial institutions. Throughout this book, a discussion on various types of Malaysian financial institutions is also relevant. While topics covered in this book might have been found in more advanced textbooks on financial institutions, the explanation and illustrations are aimed for the Malaysian perspectives. The book begins with an overview of the Malaysian financial system, through which discussion on the financial statements of financial system, mainly focusing on the sources and uses of financial institutions available in Malaysia. We also emphasize on our central bank, Bank Negara Malaysia: its relationship with the financial system. This book also includes the discussion on bank and non-bank financial institutions available in the Malaysia's financial landscape. As a Muslim country that widely used and practice Islamic activity, we also highlight a special feature of bank; Islamic bank. This book also discusses the interest rates, bank management and risk that associates with the financial institutions. We hope that readers who are looking more details information on the Malaysian financial institutions may find this book as useful. We accept all errors, and hope any errors discovered will be brought to our attention.